2018
DOI: 10.1111/1750-3841.13963
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Residual Air and Viscosity on the Rate of Heat Penetration of Retort Food Simulant in Pouch When Using Static and Oscillating Motions

Abstract: This research can be applied to food manufacturers that are retorting foods in pouches. Residual air in pouches has been studied previously; however, with the development of new retort motions, more research needs to be conducted about the effect of residual air in a pouch using the different motions. Food manufacturers can use this information to optimize their amount of residual air based on their product viscosity and retort motion. This could dramatically lower processing time which would save money and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Also, there is an observed positive correlation between cooking time and texture, as well as intactness, while a negative correlation exists with washed‐drained weights, showing that slower‐cooking beans have superior canning quality (Bassett et al ., 2020). These findings align with prior research that oscillating motion increased the average heating slope and decreased processing time than static mode (MacNaughton et al ., 2018a, 2018b). In another study, the autoclaving of Shrimp Kuruma in over‐pressure auto‐clave was conducted at various F o values (7, 8 and 9) in retort pouches and aluminium cans with the same weight and lethality to standardise the process parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is an observed positive correlation between cooking time and texture, as well as intactness, while a negative correlation exists with washed‐drained weights, showing that slower‐cooking beans have superior canning quality (Bassett et al ., 2020). These findings align with prior research that oscillating motion increased the average heating slope and decreased processing time than static mode (MacNaughton et al ., 2018a, 2018b). In another study, the autoclaving of Shrimp Kuruma in over‐pressure auto‐clave was conducted at various F o values (7, 8 and 9) in retort pouches and aluminium cans with the same weight and lethality to standardise the process parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced cooking time yields superior flavour, enhanced nutritional content, and reduced moisture loss, as highlighted in the research conducted by MacNaughton et al . (2018a, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The thickening of pre-thermal processing batters due to the increase in hydrocolloid content likely increased the resistance to heat, leading to lower lethality and C 100 when the foods were processed under the same time and temperature conditions. Previous research of the effect of viscosity on heat penetration found that increased food thickness decreased the average heating slope and increased the amount of time required to thermally process food [35]. This suggests that thinner food consistencies may benefit production facilities by decreasing the amount of time to process a food product, which could allow for more products to be made in the same amount of time.…”
Section: Thermal Processing Controls and Characteristics Of Canned Pet Foodmentioning
confidence: 94%
“…Container parameters such as dimensions, headspace (when using rotary retorts), vacuum, number of residual gases, and maximum thickness are also important to examine and control (IFTPS, 2014 ; Llosa Sanz, 2017 ). Other variables such as the rotary axis and time from filling to processing are also necessary to monitor and control (MacNaughton et al., 2018 ; May & Chappell, 2002 ; Meng & Ramaswamy, 2007 ).…”
Section: Process Calculations To Ensure Food Safetymentioning
confidence: 99%
“…Several retorting processes have investigated residual air and viscosity. One study compared static and reciprocation oscillations during the thermal treatment of flexible retort pouches (MacNaughton et al., 2018 ). The researchers discovered that agitated stirring resulted in higher heat penetration rates at all viscosities, with a reduction of up to 27% in processing time compared to static.…”
Section: Research Comparisonsmentioning
confidence: 99%